A PROPOSED FRAME OF REFERENCE FOR RESEARCH OF SAME-DIFFERENCE IN CROSS-CULTURAL COMMUNICATION AND PRAGMATIC FAILURE IN INTERCULTURAL COMMUNICATION: RESEARCH DEVELOPMENT (ARTICLE 7) - Nguyen, Quang (VNU Journal of Foreign Studies, 2025)
Following Article 6 that presents epistemological preliminaries of: (a) dynamics in culture-communication correlation, (b) co-activation within and among types of components, and (c) orientation of to-life and to-research process, this article introduces a matrix proposed for research of ‘Languages and Cultures in Interaction’ (LCI) with impact-manifestation grid in the foreground. It further propounds two process models for LCI research, of which model A focuses only on pragma-cultural expressions while model B covers both pragma-linguistic strategies and pragma-cultural expressions.